Fluid responsiveness in children with Septic shock is not a Reliable Predictor of outcome: Single Center Experience - Sally Kamal Ibrahim Ishak; Rodina Sobhy Mandour; Ahmed Said Behairy; Doha Elsayed Saad Elsherbiny; Elshimaa Salah Ahmed (Cairo University, Faculty of Medicine, Department of Pediatrics, 2023)
Background: Fluids are an integral line of management of septic shock as circulatory instability and myocardial dysfunction are the major causes of death in septic shock. Several indicators of fluid responsiveness (FR) have been proposed. Aim of the Work: to assess predictive value of assessment of fluid responsiveness on outcome of children with sepsis. Methods: This study was a prospective observational cohort study which was conducted on 25 children who were admitted to Pediatric Intensive Care Unit with septic shock at Children Hospital, Cairo University from February 2020 to May 2020. All underwent bedside echocardiography assessment of fluid responsiveness (FR) using inferior vena cava's (IVC) diameter: distensibility, collapsibility, variability indices and time velocity integral across aortic valve before and after fluid resuscitation. Results: The mean age ± SD of the studied cohort was 33.72 ± 39.65 months, 17 (68%) were males and 8 (32%) were females. All patients presented by septic shock, of them 13 (52%) were fluid responsive and 12(48%) were fluid nonresponsive (p=0.118). FR was different between ventilated patients and non-ventilated patients as regards IVC variability % before and after IV fluids (p= 0.001) and (p=0.001) respectively, stroke volume and cardiac output after IV fluids (p =0.033) and (p=0.001) respectively. FR correlated with central venous pressure measurements (p=0.000017) and inotropic support (p=0.0074) but not with main diagnosis of septic shock, mechanical ventilation of patients or not and not with number of system failure. Ten (40%) of them were on mechanical ventilation and inotropes. Nineteen (76%) improved and 6 (24%) died. There was no correlation between FR and outcome (p= 0.316). Conclusion: Bedside echocardiography may be a useful non-invasive method for follow up, evaluation of fluid responsiveness in children septic shock and to assess CI which helps in assessment of fluid response, make decision on medication, and help evaluate the different forms of shock, but it has no significant relation to the outcome of these children. Outcome of septic shock is multifactorial, depends on timing of diagnosis, fluid administration, inotropic support, and cardiac condition not fluid responsiveness only.